Study of the usability of internet technology in receptive tourism in Lima-Peru - Morales, Mery (2013)
Studies done in Ayacucho in 2005, on information technologies applied to tourism websites and contemplate just email. This paper focuses on the study to determine the usability of the internet to attract foreign tourists and problems of its use in retail and wholesale agencies. The study shows that the level of usability of technology is: the web is more informative in both sectors, the services only register online orders, answer e-mail, e-commerce agencies made little baskets wholesale ordering and electronic payment instead the retail agencies perform a greater percentage of basket orders and electronic payments, staff from both agencies have a very adequate level of preparation on the most used language in web pages is Spanish on electronic commerce issues that affect the use of the technologies are cost wholesale agencies and retail agencies procedures.